2013
DOI: 10.1371/journal.pmed.1001509
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ANRS-12126 Male Circumcision Project with HIV Levels among Men in a South African Township: Evaluation of Effectiveness using Cross-sectional Surveys

Abstract: Betran Auvert and colleagues report findings from the Bophelo Pele project, a community-based HIV prevention intervention offering free voluntary medical male circumcision (VMMC), that demonstrate an association between VMMC roll-out and a reduction in the incidence and prevalence of HIV in the community. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 28 publications
3
90
0
1
Order By: Relevance
“…In particular, Boyle and Hill failed to point out that the significant absolute adjusted risk reduction of 1.3% (actually 1.8%) was for the 2-year point of the RCTs. Follow-up studies have shown continuation, even enhancement, of the protective effect of MC against HIV with time (Auvert et al, 2013;Gray et al, 2012;Mehta et al, 2013). One might, therefore, expect a 1.3% (or rather 1.8%) reduction after 2 years to increase to 13% (or rather 18%) by 20 years.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, Boyle and Hill failed to point out that the significant absolute adjusted risk reduction of 1.3% (actually 1.8%) was for the 2-year point of the RCTs. Follow-up studies have shown continuation, even enhancement, of the protective effect of MC against HIV with time (Auvert et al, 2013;Gray et al, 2012;Mehta et al, 2013). One might, therefore, expect a 1.3% (or rather 1.8%) reduction after 2 years to increase to 13% (or rather 18%) by 20 years.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, Boyle and Hill failed to point out that the significant absolute adjusted risk reduction of 1.3% (actually 1.8%) was for the 2-year point of the RCTs. Follow-up studies have shown continuation, even enhancement, of the protective effect of MC against HIV infection with time [119] [120] [121]. One might therefore expect a 1.3% (or 1.8%) reduction after 2 years to increase to 13% (or 18%) by 20 years.…”
Section: What Makes An Expert?mentioning
confidence: 99%
“…Biological studies have shown that the delicate tissue of the foreskin is vulnerable to microscopic lesions, which increases the risk of contracting HIV (Silverman, 2004). The foreskin also houses specialised Langerhans cells, which HIV and other pathogens can readily attach to (Halperin & Bailey, 1999;El-Hout & Khauli, 2007;Bhattacharjee, 2008;Auvert et al, 2013). Studies have shown that, by removing the foreskin, a man's risk of contracting HIV through peno-vaginal penetrative sexual intercourse may be reduced by approximately 60% (Bailey, Plummer & Moses, 2001;Siegfried et al, 2003;Auvert et al, 2005;Williams et al, 2006;Bonner, 2007;El-Hout & Khauli, 2007;Schoen, 2007).…”
Section: Vmamc For Hiv Preventionmentioning
confidence: 99%